Dynamics of Human Relationships in the Fiction of Kamala Markandaya: A Post – Modern Scrutiny: Examining the Impact of Kamala Markandaya's Fiction on Human Relationships in a Post-Modern Society (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Kamala Markandaya has successfully represented and depicted human relationship in her novels. Keeping her works and the major themes, I would like to evaluate its significance in this post - modernist society. Her portrayal of human relations and human bonds is remarkable as she allows her characters to follow their own minds and face life naturally and bravely.